Pemilihan Tingkat Tutur Bahasa Jawa Pada Masyarakat Desa Klapaduwur Blora - sriwahyu istana trahutami (Universitas Aki, 2016)
This study discusses the reality in the society of Klapadhuwur village Blora regency in accordance with the use of Javanese language based on the distribution of speech level variation or undha usuk basa, which is divided into thre, namely ngoko, madya, dan krama. This study aims to describe the choosing of speech level (undha usuk)of Javanese language on the native people of Klapadhuwur village Blora regency. Data were collected using simak and cakap method. The writer also conducted observation which was done based on observer’s paradox, i.e observing how people spoke when they did not realize that they were being observed, so the speeches used were natural and genuine. At data analysis stage, equal method or identity method was used. The method of data analysis result presentation used informal method, namely formulation using ordinary words. The researcher concluded that language is the reflection of the users’ culture since the language itself is part of culture. The existence of the very complex and extensive speech level system in Javanese language can be considered as the sign of the importance of pentingnya courteousness composed in personal relationship system on Javanese people. On Klapadhuwur society, language style of ngoko is chosen to communicate at the informal activities, while at formal situation Javanese language of krama is used concurently with the use of Indonesian language. Keywords: speech level, Javanese language, society, sociolinguistics